2016
DOI: 10.3390/ijerph13060575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Al2O3 on the Toxicity and Oxidative Stress of Copper towards Scenedesmus obliquus

Abstract: Nano-Al2O3 has been widely used in various industries; unfortunately, it can be released into the aquatic environment. Although nano-Al2O3 is believed to be of low toxicity, it can interact with other pollutants in water, such as heavy metals. However, the interactions between nano-Al2O3 and heavy metals as well as the effect of nano-Al2O3 on the toxicity of the metals have been rarely investigated. The current study investigated copper toxicity in the presence of nano-Al2O3 towards Scenedesmus obliquus. Super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…An increase in MDA content was also shown in our previous studies [ 16 , 17 ] and in other studies [ 47 , 48 , 49 , 50 , 51 , 52 ]. Li et al [ 47 ] showed that MDA content of Pavlova viridis was increased significantly from 0.5 mg/L of copper and 3.25 mg/L of zinc.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…An increase in MDA content was also shown in our previous studies [ 16 , 17 ] and in other studies [ 47 , 48 , 49 , 50 , 51 , 52 ]. Li et al [ 47 ] showed that MDA content of Pavlova viridis was increased significantly from 0.5 mg/L of copper and 3.25 mg/L of zinc.…”
Section: Resultssupporting
confidence: 89%
“…Soto et al [ 48 ] evaluated the effect of copper and zinc on P. subcapitata lipid peroxidation using thiobarbituric acid reactive substances assay and reported a significant malondialdehyde increase at 0.025 mg/L copper and 0.1 mg/L zinc. Li et al [ 49 ] found that 1.0 mg/L of Al 2 O 3 NPs had a less effect on MDA production, whereas at high copper concentrations, high MDA productions were measured from both Cu and Cu + Al 2 O 3 exposure systems. Srivastava et al [ 50 ] reported an increase in the content of MDA when Hydrilla verticillata exposed to copper.…”
Section: Resultsmentioning
confidence: 99%
“…Other publications indicate the opposite pattern, namely a reduction in metal ion-induced effects in the presence of nTiO 2 or Al 2 O 3 NP in algae [ 208 , 209 ] or mussels [ 210 ], with an even more pronounced reduction in the presence of DOM [ 211 ]. Follow-up studies suggested that the direction and magnitude of effects caused by a combined exposure of TiO 2 NP and metal ions are triggered by the charge of the most toxic metal ion [ 212 ].…”
Section: Interactions Of Nanoparticles In a Complex Environmentmentioning
confidence: 99%
“…High TiO 2 NPs concentration effectively reduced the soluble Zn(II) (and its toxicity) concentrations by adsorbing Zn(II) on ENPs and settling to the bottom of the reactor [129]. Growth inhibition, oxidative stress and Cu(II) uptake by Scenedesmus obliquus were lower in mixture exposure with Al 2 O 3 NPs [143]. TiO 2 NPs reduced the toxicity of Cd(II) to bacterium Escherichia coli and the combined toxicity decreased with the increasing TiO 2 NPs concentrations, which can be explained by the reduction of the free Cd(II) concentration in the exposure medium [111].…”
Section: Reduction Of the Toxicity/bioavailability Of Metallic Pollutmentioning
confidence: 99%